The development of the Reflecting Team Utterances Framework: Process, reflections and applications. Issue 2 (30th July 2021) - Constable, Chloe; Delaney, Claire; Clutterham, Adam; Markiewicz, Abi
Abstract: The Reflecting Team (RT) has been a common companion of systemic practitioners since Tom Andersen first described its use (Andersen, 1987). Despite the widespread acceptance of such ideas in modern Systemic Practice, there is limited research into the RT method. We hoped to contribute to the broader research aim of exploring how and why reflecting team conversations lead to change by addressing the following question: is it possible to reliably categorise the utterances of the RT to form a framework? We used a content analysis to analyse and categorise over three hours of reflecting team conversations from four different clinical teams. This resulted in the identification of eleven discrete categories including: 'they asked a question to you as a family', 'they highlighted something positive and they commented on their own emotions'. We go on to discuss potential applications of this Reflecting Team Utterances Framework and our reflections on the process. Practitioner points The Reflecting Team Utterances (RTU) framework enables clinicians to facilitate discussion with trainees about the nature of a reflecting team and the categories of reflection and their potential for impact. The framework may be a useful tool within teams as a way of reflecting on the utterances chosen by teams and to facilitate discussion around this. Questions such as "what are we most often saying and why" could add to supervisory discussions extending therapists' repertories in reflecting and ensuring reflexivity regarding intentionality. There is a potential to use the framework also with families, asking questions prior to reflecting teams such as 'What feels most useful to you at this time; connections with our own experiences or suggestions about what you could experiment with?'